Geopolitical risks and their impact on global macro-financial stability: Literature and measurements - Martin Hodula; Jan Janků; Simona Malovaná; Ngoc Anh Ngo (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
In our paper, we provide a review of the literature to identify the main transmission channels through which geopolitical risks (GPR) influence m a cro-financial st ab ility. We be gi n by analyzing the existing measures of geopolitical tensions and uncertainty, showing that GPR impacts economic and financial u n certainty e p isodically, w i th s i gnificant bu t tr an sient spikes during major geopolitical events. The review then identifies t he t wo p rincipal c hannels through which GPR affects macro-financial s t ability: t he fi nancial ch an nel, op erating th rough increased uncertainty and heightened risk aversion, leading to shifts in investment portfolio allocations and cross-border capital flows; a nd t he r eal e conomy c hannel, impacting global trade, s upply chains, and commodity markets. Using data from the past two to three decades, we provide graphical analyses that confirm t he fi ndings in the literature, hi ghlighting the episodic nature of the impact of GPR. These insights underscore the need for policymakers and financial i nstitutions t o adopt event-specific a p proaches t o e f fectively m i tigate t h e a d verse e f fects o f g e opolitical r i sks on economic and financial systems.
urn:nbn:fi-fe2024092574809
Keywords: D80; E32; F44; F51; G2; G15; H56; 330; Financial stability; geopolitical risk; global economy; macro-financial impact; uncertainty shocks